Computational close up on protein–protein interactions: how to unravel the invisible using molecular dynamics simulations?. (27th July 2015) - Rakers, Christin; Bermudez, Marcel; Keller, Bettina G.; Mortier, Jérémie; Wolber, Gerhard
Abstract : As an essential part of many biological processes, protein–protein interactions (PPIs) offer exciting and promising opportunities for drug discovery by extension of the druggable target space. Over the last decade, studies on protein networks have significantly increased the number of identified PPIs. However, despite steadily growing data on PPIs, detailed understanding of the interaction surfaces and their dynamics remains limited. Furthermore, the development of small‐molecule inhibitors of PPIs faces technological challenges, leaving the question about the 'druggability' of PPIs open. Molecular dynamics (MD) simulations may facilitate the prediction of druggable binding sites on protein–protein interfaces by detecting binding hot spots and transient pockets. MD allows for a detailed analysis of structural and functional aspects of PPIs and thus provides valuable insights into PPI mechanisms and supports the design of PPI modulators. We provide an overview on the main areas of MD applications to PPIs including structural investigations and the design of PPI disruptors. Emphasizing the beneficial synergies between computational and experimental techniques, MD techniques are also frequently applied to low‐resolution structural data and have been used to elucidate structure and movements of complex macromolecular structures relevant for biological processes. WIREs Comput Mol Sci 2015, 5:345–359. doi: 10.1002/wcms.1222 This article is categorized under: Structure and Mechanism > Molecular Structures Molecular and Statistical Mechanics > Molecular Dynamics and Monte-Carlo Methods Molecular and Statistical Mechanics > Molecular Interactions Abstract :